2009
DOI: 10.1103/physrevb.79.235131
|View full text |Cite
|
Sign up to set email alerts
|

Detecting charge and lattice dynamics in photoinduced charge-order melting in perovskite-type manganites using a 30-femtosecond time resolution

Abstract: We investigated the ultrafast dynamics of photoinduced melting of charge and orbital order in a perovskitetype manganite, Nd 0.5 Ca 0.5 MnO 3 , by means of pump-probe reflection spectroscopy. By irradiation with a 20-fs laser pulse, only the charge sectors become melted within ϳ30 fs through strong electron correlations. During this process the oxygen displacements associated with the ordered phase persist. These displacements are subsequently released accompanied by several coherent oscillations. The coherent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 36 publications
3
45
1
Order By: Relevance
“…This ultra-fast CO melting and generation of a metallic state are consistent with the recent pump-probe experiments in manganite; a melting of charge order within about 30fs by irradiation was observed. 19 We note that the weakening of the NN spin correlation within few fs is not contradict to the magneto-optical Kerr spectroscopy measurement. In several charge ordered manganites, it was shown that the photo-induced spin dynamics observed by the Kerr spectroscopy is slower than the photo-induced charge dynamics probed by the optical reflection.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 88%
See 3 more Smart Citations
“…This ultra-fast CO melting and generation of a metallic state are consistent with the recent pump-probe experiments in manganite; a melting of charge order within about 30fs by irradiation was observed. 19 We note that the weakening of the NN spin correlation within few fs is not contradict to the magneto-optical Kerr spectroscopy measurement. In several charge ordered manganites, it was shown that the photo-induced spin dynamics observed by the Kerr spectroscopy is slower than the photo-induced charge dynamics probed by the optical reflection.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 88%
“…The positive and negative signs of iγ in the denominators of Eq. (19) are for the cases of τ < τ D and τ > τ D , respectively. We focus on the first term in Eq.…”
Section: Model and Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…One typical example is coherent oscillations observed after the rapid photoinduced changes. [10][11][12][13][14][15][16][17] These oscillations involve much information of characteristic collective modes of the systems, phonon, orbiton, and so on. Hence investigating the coherent oscillations provides us insight into roles of these modes in the photoinduced phenomena.…”
mentioning
confidence: 99%